Osteoporosi: la malattia e il suo costo sanitario - Zara, Gianpaolo; Della Pepa, Carlo; Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2002)
Osteoporosis is a disorder of bone re-modeling, characterized by loss of its micro-architecture and decreased bone density, which lead to fragility and high risk of fracture following moderate traumata. Osteoporosisrelated pathological fractures occur more frequently in post-menopausal women, and the WHO estimates that the risk of osteoporotic fractures in women is approximately 40% during lifetime. The prevention of these osteoporotic fractures is considered one of the primary objectives for the control of the economical health burden of modern societies. The first part of this paper briefly outlines the physio-pathological basis, the epidemiology, the diagnosis and the available treatment options for osteoporosis, with particular regard to those therapies that are able to reduce the incidence of pathological fractures, that represent the main cost factor of the disease. In the second part, we reviewed the economical evaluations published on the cost of illness and of the costefficacy of the treatments. The studies that have analyzed the cost of osteoporosis, although incompletely, highlight that the greatest expenditures are related to hospitalization and rehabilitation after hip fracture, while the cost for the pharmacological treatment is relatively low. The cost-efficacy and cost-utility analyses conducted on pharmacological treatment are quite heterogeneous, and therefore hardly comparable, beside being conducted in countries with different health systems; the obtained data are nor directly transferable to the Italian setting. However, it emerges that diphosphonates, estrogens and SERMs (selective estrogen receptor modulators) are among the drugs with more favorable cost/effectiveness ratio, but there is still an uncertainty in the detection of the appropriate patient groups, which is crucial for the clinical, economical and ethical optimization of prevention interventions.